An ecological risk assessment for a South African acid mine drainage - Jooste, Sebastian; Thirion, Christa (Water science and technology, 1999)
Biotic integrity assessment of a stream subject to acid mine drainage (AMD) indicated that a number of the expected taxa were absent. Acute and chronic toxicity assessment of water sampled in a stream subject to AMD impact indicate that even at near neutral pH the metal concentration in the water dominates the toxicity toward Daphma pulex. Extending the observation period to the death of test cohort in an otherwise standard sub-chrome toxicity test, allowed for generating a life table for the D. pulex. The probability of population extinction was estimated from the statistical characteristics of a bootstrap estimation of the dominant eigenvalue of a Leslie matrix based on the life table. At the current concentration levels of metals, notably manganese and zinc, in the water, a high risk to aquatic life exists. It is suggested that the metal content of the stream water also be addressed in an AMD water treatment plan.